2013
DOI: 10.1111/bju.12269
|View full text |Cite
|
Sign up to set email alerts
|

Importance of HOX genes in normal prostate gland formation, prostate cancer development and its early detection

Abstract: • The aims of this paper were to review the published literature on the role of HOX genes in the development of the normal prostate gland and in prostate cancer and to discuss the potential role of the HOX family member, Engrailed-2 (EN2), as a diagnostic test of PCa.• Hox genes were first described in the fruit fly Drosphila melanogaster, where they specify the body plan and control the formation of body segments. They belong to a family of homeodomain-containing transcription factors that determine cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 44 publications
1
46
0
3
Order By: Relevance
“…HOX genes are developmental genes shown to be master regulatory transcription factors involved in embryogenesis . A number of HOX genes are essential in the development of the prostate gland and their expression pattern is altered in prostate cancer . A genomic pathway analysis has showed that loss of the HOXA9 co‐factors PBX1 , MEIS1 and MEIS2 are associated with prostate tumorigenesis and progression .…”
Section: Discussionmentioning
confidence: 99%
“…HOX genes are developmental genes shown to be master regulatory transcription factors involved in embryogenesis . A number of HOX genes are essential in the development of the prostate gland and their expression pattern is altered in prostate cancer . A genomic pathway analysis has showed that loss of the HOXA9 co‐factors PBX1 , MEIS1 and MEIS2 are associated with prostate tumorigenesis and progression .…”
Section: Discussionmentioning
confidence: 99%
“…The HOX gene family includes various transcription factors that help to determine cell and tissue identity in the early development of PC [35], and increase greatly during the development of PC [36]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition several members of the HOX family (e.g., HOXB6 , B7 ) that belong to this subnetwork, are involved in PC onset [35] or development [36]. …”
Section: Resultsmentioning
confidence: 99%
“…It is a heterogeneous disease with regard to clinical course and molecular alterations (Al-Maghrebi et al , 2012). The tests used in clinical practice to diagnose PCa, including the measurement of serum PSA, DRE and TRUS-guided biopsies, have significant limitations (Javed and Langley, 2013). More than 60% of biopsies conducted based on PSA test results ultimately turn up negative (Altintas et al , 2013).…”
Section: Discussionmentioning
confidence: 99%